Planning for Private Forest Development Based on Community Empowerment in Malang Regency - Rosyidatuzzahro Anisykurlillah; Tjahjanulin Domai; Romy Hermawan (Postgraduate School Universitas Brawijaya, 2020)
This research aimed to describe and analyze the planning formulated by Malang region Forestry Service Branch (CDK Wilayah Malang) for private forest development based on community empowerment in Malang Regency. One of the targets of forestry revitalization is by building and developing private forests through community empowerment-based programs or activities. This qualitative research is descriptive analysis and the data collection techniques are interviews, observation, and documentation study. Then, they were analyzed using an interactive model. It was found that the planning process for private forest development in Malang Regency is still not effective. This is because the government formulated planning is dominated by top-down planning and technocratic. In the formulation process, it doesn't involve the community. Other constraints are limited data and lack of funding allocation.